Traditional Chinese medicine use in patients with oral cancer: A retrospective longitudinal cohort study in Taiwan. Issue 38 (23rd September 2022) - Ben-Arie, Eyal; Lottering, Bernice; Inprasit, Chanya; Yip, Hei-Tung; Ho, Wen-Chao; Ton, Gil; Lee, Yu-Chen; Kao, Pei-Yu
Abstract : Oral cancer is frequently associated with smoking, alcohol consumption, and betel quid chewing, which are common harmful behaviors observed in certain cohorts of the Taiwanese population. Some reports have explored the potential therapeutic effect of certain herbal remedies on cancer treatments and the outcomes thereof. However, supportive evidence regarding the specific use of traditional Chinese medicine (TCM) in oral cancer treatment is lacking and deserves further investigation. This study measured the use of TCM therapies for oral cancer in a Taiwanese population-based retrospective longitudinal cohort study. The Taiwan National Health Insurance Research Database was utilized to conduct this study. The study population was limited to oral cancer patients diagnosed between 2000 and 2009, which were followed up for at least 5 years. Therapeutic strategies investigated included acupuncture and the Chinese herbs and formula used. Additionally, the frequency of TCM treatment visits, total medical costs, and all-cause mortality were also analyzed. Between 2000 and 2009, a total of 951 patients were diagnosed with various oral cancers. 13.7% of the diagnosed patients utilized TCM treatment measures. The majority of the patients were males. The top 3 common single herbs used were Xuán shēn (Radix Scrophulariae), Shí hú (Herba Dendrobii), and Mài mén dōng (Ophiopogon Japonicus ). Then, Gān lù yǐn, Zhī bǎi dì huáng wán, and Sàn zhǒng kuì jiān tāng were the most frequently used herbal formulas. The survival probability was higher in TCM users when compared to non-TCM users in 5- and 12-year all-cause mortality ( P < .05). This study explored the use of TCM therapies in oral cancer patients and identified essential information regarding the specifics of conventional herbal medicine used, affiliated medical costs, survival probability, and common symptoms observed in Taiwanese oral cancer patients.